Single-stranded RNA viruses infecting the invasive Argentine ant, Linepithema humile - Monica A. M. Gruber (Nature Portfolio, 2017)
Abstract Social insects host a diversity of viruses. We examined New Zealand populations of the globally widely distributed invasive Argentine ant (Linepithema humile) for RNA viruses. We used metatranscriptomic analysis, which identified six potential novel viruses in the Dicistroviridae family. Of these, three contigs were confirmed by Sanger sequencing as Linepithema humile virus-1 (LHUV-1), a novel strain of Kashmir bee virus (KBV) and Black queen cell virus (BQCV), while the others were chimeric or misassembled sequences. We extended the known sequence of LHUV-1 to confirm its placement in the Dicistroviridae and categorised its relationship to closest relatives, which were all viruses infecting Hymenoptera. We examined further for known viruses by mapping our metatranscriptomic sequences to all viral genomes, and confirmed KBV, BQCV, LHUV-1 and Deformed wing virus (DWV) presence using qRT-PCR. Viral replication was confirmed for DWV, KBV and LHUV-1. Viral titers in ants were higher in the presence of honey bee hives. Argentine ants appear to host a range of’ honey bee’ pathogens in addition to a virus currently described only from this invasive ant. The role of these viruses in the population dynamics of the ant remain to be determined, but offer potential targets for biocontrol approaches.